Impact of network competence on firm's performances among Chinese and Indian entrepreneurs: A multigroup analysis - Tehseen, Shehnaz *; Qureshi, Zuhaib Hassan; Ramayah, T (Academy of entrepreneurship, 2018)
The aim of the current study was to analyse and compare the impact of network competence on four types of firms’ performances-perceived financial performance, perceived non-financial performance, perceived business growth and perceived performance relative to competitors-among Malaysian Small and Medium-Sized Enterprises (SMEs) run by Chinese and Indian entrepreneurs. A total of 200 retailers and wholesale owners in Klang Valley, Malaysia participated in a face-to-face survey. The collected data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) and multigroup analysis was performed to test the hypotheses developed. Findings revealed network competence to have a positive impact on all four types of firms’ performances among Chinese entrepreneurs. However, for Indian entrepreneurs, network competence was found to have a positive impact only on perceived financial performance and perceived performance relative to competitors. A significant difference was also found between Chinese and Indian entrepreneurs regarding the impact of network competence on perceived business growth.